The future of mobility : scenarios for China in 2030 - Ecola, Liisa; Zmud, Johanna; Gu, Kun; Phleps, Peter; Feige, Irene (Research report (Rand Corporation) ;, 2015)
"Researchers developed two scenarios to envision the future of mobility in China in 2030. Economic growth, the presence of constraints on vehicle ownership and driving, and environmental conditions differentiate the scenarios. By making potential long-term mobility futures more vivid, the team sought to help decisionmakers at different levels of government and in the private sector better anticipate and prepare for change"--Provided by publisher.